제12회 세계농촌사회학대회 개최 결과 보고서 - 정기환 (한국농촌경제연구원, 2008)
The World Congress of Rural Sociology was held between 6th and 11th, July in 2008 at the KINTEX in the city of Goyang, Korea. The Korean Rural Sociological Society (KRSS) and the Korea Rural Economic Institute (KREI) jointly hosted the conference. Major events during the period were opening ceremony, plenary session, special forum, welcome reception, welcome dinner, farewell dinner, and excursion. Main theme of the Congress was "Envisioning a Prosperous Rural Future in a Globalizing World." World Congress Organizing Committee and Secretariat Office were the most important acting organizations in preparing and implementing the conference. Congress homepage was open to public for pre-registration and accommodation booking. The homepage of the International Rural Sociological Association accepted abstracts of papers and session organization applications. During the Congress, 441 scholars from 48 different countries participated in the 77 sessions in total. Two hundred forty papers were presented and discussed for four days. A special forum, under the title of "Vision of Korean Agriculture and Rural Society and its Development", was also held. William Friedland, professor emeritus of the University of California at Santa Cruz, and other four renowned speakers were invited to deliver keynote speeches. A questionnaire was distributed to the participants to collect their opinions about the conference; 24% of respondents replied that they were "very satisfied," and 48% "satisfied," while only 6% said the conference were "not satisfied." Correspondence: Jang Heo (heojang@krei.re.kr), Ki-Whan Chung (kwchung@krei.re.kr)